The effect of laser shock peening, shot peening and their combination on the microstructure and fatigue properties of Ti-6Al-4V titanium alloy - Luo, Xuekun; Dang, Ning; Wang, Xin (International journal of fatigue, 2021)
[Display omitted] •The fatigue life can be significantly improved (up to 9.3 times) by (LSP+SP).•Gradient microstructure with dislocations and novel CRS distribution can be induced.•Fatigue crack initiation can be hindered by the high-density dislocation layer.•Fatigue crack growth rate can be retarded by the dislocation proliferation layer. In this work, the effect of a novel post process integrating laser shock peening (LSP) with shot peening (SP) on the fatigue property of Ti-6Al-4V titanium alloy is investigated. The fatigue life can be improved (up to 9.3 times) by this post-process. The compressive residual stress (CRS) distribution and dislocation-gradient microstructure obtained were found to be responsible for the improvement. The fatigue crack initiation was hindered by the high-density dislocation layer with high CRS value on the surface and maximum CRS in the sub-surface, while the crack propagation was retarded by the dislocation proliferation layer with large CRS gradient.